New evidence for, and challenges in, linking small CGG repeat expansion FMR1 alleles with Parkinson's disease. (25th December 2012) - Loesch, DZ; Tassone, F; Lo, J; Slater, HR; Hills, LV; Bui, MQ; Silburn, PA; Mellick, GD
Abstract : We recently reported a significant increase in the frequency of carriers of grey zone (GZ) alleles of FMR1 gene in Australian males with Parkinson's disease (PD) from Victoria and Tasmania. Here, we report data comparing an independent sample of 817 PD patients from Queensland to 1078 consecutive Australian male newborns from Victoria. We confirmed the earlier finding by observing a significant excess of GZ alleles in PD (4.8%) compared to controls (1.5%). Although both studies provided evidence in support of an association between GZ‐carrier status and increased risk for parkinsonism, the existing evidence in the literature from screening studies remains equivocal and we discuss the need for alternative approaches to resolve the issue.